Elementos benéficos sobre variáveis fisiológicas e bioquímicas em plantas de Pfaffia glomerata (Spreng.) expostas ao alumínio - Strauss, Ruziele de Quadros Sandri (2019)
The association between acid soils and metal is one of the main chemical constraints related to plant growth. Among these metals is aluminum (Al), which is limiting the growth and development of plants. In this sense, there are elements that when used in low concentrations can alleviate the damages caused by Al, such as selenium (Si) and silicon (Si). This work aimed to evaluate interference of Se or Si on the physiological and biochemical variables in plants of Pfaffia glomerata grown under Al toxicity. The plants of P. glomerata were propagated in vitro and then moved to culture in pots with sand and nutrient solution. After acclimation, different concentrations of Al (AlCl3), Se (Na2SeO4) and Si (NaSiO3) were added, forming the following treatments: T1: control (complete nutritional solution): T2: 1.85 mM Al, T3: 1.5 mM Si: T4: 1.85 mM Al + 1.5 mM Si; T5: 0.002 mM Se; T6: 1.85 mM Al + 0.002 mM Se. Afterwards plants to different treatments, samples were collected in two periods at 30 and 60 days, after which the growth variables (dry biomass, plant height, root length and density, leaf area, number of leaves) and biochemical variables (lipid peroxidation, antioxidant enzymes, hydrogen peroxide content and photosynthesis) were analyzed. The toxicity of Al reduced root length and diameter, but of the elements tested only Si was able to revert to the action of Al toxicity. Al effects were alleviated by Si in the shoot, significantly at 30 days. As for the biochemical variables, Si was more efficient in the mitigation of the metal effect, being able to stimulate the activity of the antioxidant enzymes and reducing the production of hydrogen peroxide. Already the Se presented mitigation effect of Al mainly in the roots of P. glomerata that is the part used for the extraction of phytomedicines. Thus, it has been observed that Si has a beneficial effect on plants, minimizing Al toxicity more effectively, and can be used to increase the quality of cultivation of this medicinal plant.